3-3p=4-2p

Simple and best practice solution for 3-3p=4-2p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-3p=4-2p equation:


Simplifying
3 + -3p = 4 + -2p

Solving
3 + -3p = 4 + -2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2p' to each side of the equation.
3 + -3p + 2p = 4 + -2p + 2p

Combine like terms: -3p + 2p = -1p
3 + -1p = 4 + -2p + 2p

Combine like terms: -2p + 2p = 0
3 + -1p = 4 + 0
3 + -1p = 4

Add '-3' to each side of the equation.
3 + -3 + -1p = 4 + -3

Combine like terms: 3 + -3 = 0
0 + -1p = 4 + -3
-1p = 4 + -3

Combine like terms: 4 + -3 = 1
-1p = 1

Divide each side by '-1'.
p = -1

Simplifying
p = -1

See similar equations:

| 6x^2-2x=-x+6x^2 | | 14g= | | 107-6x=12x-21 | | 375.6m= | | x^5-x+3=0 | | 97-3x=7-8x | | 2x+1=+5 | | 2x^2-6x+2x-6=0 | | 1,5=0,15 | | -6u-5=13 | | x^2+27x-28=0 | | (x+1)(2x-6)=0 | | 23s+45=19s-39 | | 7t-17=6t+16 | | 12x-4=7x+14 | | 5x+9=2x+36 | | 4-6x=6x+10 | | 4x-25=7 | | 2(a-5)+4(a-5)= | | x+5,4-2x+1.8=1,2(2-x) | | 9x-6=15+2x | | 3(x-2)=2(4x+1)-3 | | 5x+2x^2=0 | | 12x+3-4x=8x+2-3x | | ln(x)-ln(4)=11 | | X^2+10X-3200=0 | | X^2+10X-800=0 | | 2x+4+8x-3=24x+9 | | 12(9)-(10)+5= | | 12x-y+5=0 | | x+2y-0=120 | | (5c-4)(6c-6)=0 |

Equations solver categories